Heatwave impact on mortality and morbidity and associated vulnerable factors : a systematic review protocol - Fadly Syah,; Rozita Hod,; Norfazilah Ahmad,; Mazni Baharom,; Fredolin Tangang, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Heatwave can increase the risk for heat-related illnesses and mortality. Many studies showed certain population are vulnerable to heatwave such as elderly, children and low-income households. However, the findings were inconsistent. This study aims to identify the effect of heatwave on the mortality and morbidity and associated vulnerability factors. Five electronic databases (Pubmed, Ebsco Host, WOS, OVID Medline and Scopus) will be the primary searching tools to retrieve relevant literatures. An additional searching tool (Google Scholar) will be used to seek for grey literatures. Selection of literature will be based on the inclusion criteria (empirical full-text article, English language and published between 2010-2021). Two authors will be assigned in each step of the process, starting from screening of the title, abstract and full text based on the inclusion criteria, data extraction and quality appraisal. Mixed-Method Appraisal Tool (MMAT) will be utilized to assess the quality of selected articles. Meta-analysis, thematic analysis and narrative approach will be the option used to describe the findings. This study protocol is registered under PROSPERO (CRD42021232847). This study presents a reliable and valid systematic review process that identifies a comprehensive evidence-based information on impacts of heatwave on human health especially upon the vulnerable groups.